Investigation of Bulk and DTMOS triple-gate devices under 60 MeV proton irradiation - Cano de Andrade, Maria Gloria [UNESP]; Martino, Joao Antonio; Aoulaiche, Marc; Collaert, Nadine; Simoen, Eddy; Claeys, Cor (Elsevier B.V., 2014)
In this paper, the influence of proton irradiation is experimentally studied in triple-gate Bulk FinFETs with and without Dynamic Threshold MOS configuration (DTMOS). The drain current, transconductance, Drain Induced Barrier Lowering (DIBL) and the important figures of merit for the analog performance such as transconductance-over-drain current, output conductance and intrinsic voltage gain will be compared. Furthermore, the Low-Frequency (LF) noise will be also analyzed in the DT mode and the standard biasing configuration. The results indicate that the better electrical characteristics and analog performance of DTMOS FinFETs make them very competitive candidates for low-noise RF analog applications in a radiation environment. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: DTMOS FinFETs; Proton irradiation; Analog performance; Low-frequency noise; Flicker noise; Generation-recombination noise